If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3u(u + 1) = 0 Reorder the terms: -3u(1 + u) = 0 (1 * -3u + u * -3u) = 0 (-3u + -3u2) = 0 Solving -3u + -3u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '-3u'. -3u(1 + u) = 0 Ignore the factor -3.Subproblem 1
Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0Subproblem 2
Set the factor '(1 + u)' equal to zero and attempt to solve: Simplifying 1 + u = 0 Solving 1 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + u = 0 + -1 u = 0 + -1 Combine like terms: 0 + -1 = -1 u = -1 Simplifying u = -1Solution
u = {0, -1}
| 43x+24=24 | | 5z+9=-6 | | 2x-3y-5y+9x+6= | | 5p^2-33P-14=0 | | 10-8z=-2-4 | | 2(1y+3)=9y+2-4 | | 5(j-4)=-8 | | 20/y=100 | | 2w^2-8w-10=0 | | 1.5x+1.8y=29.7 | | 20=5.6 | | 5f^2+18f+9=0 | | Log(6)(3)=x | | 1x+1y=29 | | .1x+.5x=48000 | | 40x+(25-x)x=156 | | 4(6a-2)=-2(4-a) | | y=3y+9-1 | | (9x3)-(20/5) | | 10+6m=4(3+2m) | | 2x^2-22x+100=0 | | 2x-56=y | | -16+-2v=-54 | | (4n-20)+(4n+20)= | | 4y=-3(5)-8 | | 1x+44=5x+8 | | ((2x)^(1/4))^3 | | 1.30x=12+x | | 2m-3-8a=-27 | | ((2x)^1/4)^3 | | .13+m=6.7 | | 3y^2+40y-28=0 |